Rescue of Cyclic AMP Mediated Long Term Potentiation Impairment in the Hippocampus of Mecp2 Knockout (Mecp2-/y) Mice by Rolipram - Balakrishnan, Saju; Niebert, Marcus; Richter, Diethelm W. (Frontiers in Cellular Neuroscience, 2016)
Rett syndrome (RTT) patients experience learning difficulties and memory loss. Analogous deficits of hippocampal plasticity are reported in mouse models of RTT. To elucidate the underlying pathophysiology, we studied long term potentiation (LTP) at the CA3 to CA1 synapses in the hippocampus in acute brain slices from WT and Mecp2-/y mice, by either activating cAMP dependent pathway or using high frequency stimulation, by means of patch clamp. We have observed that, the NMDA channel current characteristics remain unchanged in the Mecp2-/y mice. The adenylyl cyclase (AC) agonist forskolin evoked a long lasting potentiation of evoked EPSCs in WT CA1 neurons, but only minimally enhanced the EPSCs in the Mecp2-/y mice. This weaker potentiation in Mecp2-/y mice was ameliorated by application of phosphodiesterase 4 inhibitor rolipram. The hyperpolarization activated cyclic nucleotide gated channel current (Ih) was potentiated to similar extent by forskolin in both phenotypes. Multiple tetanus induced cAMP-dependent plasticity was also impaired in the Mecp2-/y mice, and was also partially rescued by rolipram. Western blot analysis of CA region of Mecp2-/y mice hippocampus revealed more than 2 fold up-regulation of protein kinase A (PKA) regulatory subunits, while the expression of the catalytic subunit remained unchanged. We hypothesize that the overexpressed PKA regulatory subunits buffer cAMP and restrict the PKA mediated phosphorylation of target proteins necessary for LTP. Blocking the degradation of cAMP, thereby saturating the regulatory subunits alleviated this defect.